Effects of Garlic Extract, Allamanda Leaf Extract and Provax -200 on Seed Borne Fungi of Rice (The Agriculturists, 2012)
Seeds of rice were treated with Garlic (Allium sativum) clove extract @ 1:0, 1:1, 1:2 dilutions in water, allamanda (Allamanda cathartica) leaf extract @ 1:1, 1:2, 1:3 dilutions in water and Provax-200 @ 0.3% for controlling seed borne fungi, where the seed samples of three rice varieties viz. Katharee, Gutee Aus and Kalijira were collected from farmers storages of Bangladesh. The seed germination under control ranged from 64 to 77%, where treatments resulted up to 100% germination. The identified seed borne fungi of rice were Bipolaris oryzae, Curvularia oryzae, Fusarium oxysporum, F. moniliforme, Nigrospora oryzae, Aspergillus flavus, Aspergillus niger and Penicillium sp., where prevalence of Bipolaris oryzae (7.5%) and Fusarium moniliforme (8.3%) were the maximum. All the treatments significantly reduced the seed borne fungi up to 100% over the control, where Provax was found best and was statically similar to garlic (1:1) extract against seed borne pathogen of rice.DOI: http://dx.doi.org/10.3329/agric.v10i1.11064The Agriculturists 2012; 10(1): 46-50